Confinement of the 0.5…4.5 keV plasma ions in low density discharges of the U-3M torsatron - Dreval, M.; Slavnyj, A.S. (Вопросы атомной науки и техники, 2012)
Dependences of the charge exchange (CX) fluxes of neutral are investigated via neutral particle analyzers (NPA) in the U-3M torsatron. Fast (≤0.5 ms) decay of the vertical and tangential CX fluxes has been observed after turning off RF heating power. According to these measurements, the U-3M energy confinement time of the 0.5…4.5 keV ions is less than 0.5 ms in the low density (ne=(1…4)·10¹² cm⁻³) discharges. No difference between confinement of the ion energy component parallel to the magnetic field and confinement of the perpendicular to the magnetic field one was observed in U-3M. Evidently, an ion cooling through CX collisions with neutrals sustain the main channel of the 0.5…4.5 keV ion energy loss in the U-3M torsatron. Зависимости потоков нейтралов перезарядки измерены с помощью анализаторов нейтральных частиц в торсатроне У-3М. Быстрое (≤0.5 мс) время спада вертикального и тангенциального потоков нейтралов перезарядки наблюдалось после выключения мощности ВЧ-нагрева. Согласно этим измерениям время удержания энергии 0.5…4.5 кэВ ионов в У-3М меньше, чем 0.5 мс в низкоплотных (ne=(1…4)·10¹² cm⁻³) разрядах. В У-3М не было обнаружено разницы между удержанием компонентов ионной энергии параллельной и перпендикулярной магнитному полю. По-видимому, остывание ионов посредством актов перезарядки с нейтралами является основным каналом потери энергии 0.5…4.5 кэВ ионов в торсатроне У-3М. Залежності потоків нейтралів перезарядки виміряні за допомогою аналізаторів нейтральних частинок у торсатроні У-3М. Швидкий (≤0.5 мс) час спаду вертикального і тангенціального потоків нейтралів перезарядки спостерігався після виключення потужності ВЧ-нагріву. Згідно цим вимірам час утримання енергії 0.5…4.5 кеВ іонів в У-3М менший, ніж 0.5 мс у розрядах з малою густиною (ne = (1…4)·10¹² cm⁻³). B У-3М не було виявлено різниці між утриманням компонент іонної енергії паралельної та перпендикулярної магнітному полю. Мабуть охолодження іонів за допомогою актів перезарядки з нейтралами є основним каналом втрати енергії 0.5…4.5 кеВ іонів у торсатроні У-3М.